Relationship between kinematic characteristics and free-throw shooting precision: markerless motion capture analysis - Templin, T.; Cabarkapa, D.; Miller, J.; Cabarkapa, D.; Fry, A.; Eliason, T.; Frazer, L.; Medjaouri, O.; Chambers, D.; Saylor, K.; Nicolella, D. (ISBS Proceedings Archive (Michigan), 2023)
The search for aspects of basketball shooting that characterize successful performance is an area of focus for sports biomechanists. However, the systematic evaluation of these key elements during shooting practice is limited due to the time it takes to collect and/or process the data. Thus, the purpose of the present study was to evaluate the relationship between some of the key kinematic variables extracted from a markerless motion capture system on free-throw shot performance. Multivariable linear regression analysis indicated that shot plane alignment, trunk rotation, entry angle, and timing of elbow extension were some of the key contributors to free-throw shot precision. Overall, these kinematic variables serve as a preliminary set of outcomes that can be reported to coaches and players that decide to use markerless motion capture technology for free-throw shooting biomechanical analysis.